2004
DOI: 10.1007/bf03030220
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mobilization of a maize transposable family,Ac/Ds, in pepper using In Vivo transient assay system

Abstract: A maize transposable family, Ac/Ds, has been successfully utilized as a mutagenizing agent not only in monocot but also in dicot. In order to develop insertional mutagenesis system in pepper, the mobility of Ac/Ds has been examined. In this study, the excision of the elements was monitored via transient assay system with protoplasts. Two different systems were developed and compared; one-and two-elements systems. In a one-element system, Ac alone was introduced into cells. As a two-element system, Ac and Ds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Recently, however, we isolated mesophyll protoplasts from pepper and introduced the maize transposable family, Ac/Ds, by PEG treatment to examine its mobility in pepper nuclei. The results showed that both Ac and Ds elements were highly mobile in pepper protoplasts (Kim et al 2004a). Therefore, we are interested in studying the transposition of the Ac/Ds element with a long term goal of developing a gene tagging system and a method for transposon mutagenesis in pepper.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, however, we isolated mesophyll protoplasts from pepper and introduced the maize transposable family, Ac/Ds, by PEG treatment to examine its mobility in pepper nuclei. The results showed that both Ac and Ds elements were highly mobile in pepper protoplasts (Kim et al 2004a). Therefore, we are interested in studying the transposition of the Ac/Ds element with a long term goal of developing a gene tagging system and a method for transposon mutagenesis in pepper.…”
Section: Introductionmentioning
confidence: 96%